2020
DOI: 10.1128/msystems.00562-19
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Response of Nitrosomonas europaea Transitioned from Ammonia- to Oxygen-Limited Steady-State Growth

Abstract: Ammonia-oxidizing microorganisms perform the first step of nitrification, the oxidation of ammonia to nitrite. The bacterium Nitrosomonas europaea is the best-characterized ammonia oxidizer to date. Exposure to hypoxic conditions has a profound effect on the physiology of N. europaea, e.g., by inducing nitrifier denitrification, resulting in increased nitric and nitrous oxide production. This metabolic shift is of major significance in agricultural soils, as it contributes to fertilizer loss and global climate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 90 publications
(152 reference statements)
2
42
0
Order By: Relevance
“…The elevated cytochrome c activity of oxygen-deprived N. eutropha and Nitrosospira fit well with the results reported by Sedlacek et al [9] and Pellitteri-Hahn et al [16], whose works indicated a significant increase in the cytochrome c content of stressed cells, but contradicted Wei et al [22], who reported mRNA levels for cytochrome c in growing cells to exceed those of energy-starved cells by a factor of 10. Sedlacek et al [9] used transcriptomics on stressed N. europaea to elucidate the stress The different oxygen profiles corresponding to aerated (+O 2 ) and oxygen-deprived (−O 2 ) culture conditions in Figures 3a and 4a were the result of an interplay of two sequential processes, namely oxygen transfer at the air-liquid interphase and dissolved oxygen consumption in the liquid medium [48]. In the incubation with shaking (+O 2 ), the oxygen transfer at the air-liquid interphase was higher compared to the non-shaking condition, which led to a higher oxygen concentration in the medium throughout the entire growth experiment.…”
Section: Effects Of Oxygen Stress On the Cytochrome-c Content Of Nitrsupporting
confidence: 90%
See 4 more Smart Citations
“…The elevated cytochrome c activity of oxygen-deprived N. eutropha and Nitrosospira fit well with the results reported by Sedlacek et al [9] and Pellitteri-Hahn et al [16], whose works indicated a significant increase in the cytochrome c content of stressed cells, but contradicted Wei et al [22], who reported mRNA levels for cytochrome c in growing cells to exceed those of energy-starved cells by a factor of 10. Sedlacek et al [9] used transcriptomics on stressed N. europaea to elucidate the stress The different oxygen profiles corresponding to aerated (+O 2 ) and oxygen-deprived (−O 2 ) culture conditions in Figures 3a and 4a were the result of an interplay of two sequential processes, namely oxygen transfer at the air-liquid interphase and dissolved oxygen consumption in the liquid medium [48]. In the incubation with shaking (+O 2 ), the oxygen transfer at the air-liquid interphase was higher compared to the non-shaking condition, which led to a higher oxygen concentration in the medium throughout the entire growth experiment.…”
Section: Effects Of Oxygen Stress On the Cytochrome-c Content Of Nitrsupporting
confidence: 90%
“…Microbial nitrification, i.e., the metabolization of ammonia to nitrite, performed by AOB under aerobic conditions is crucial for the biological treatment of wastewater [2]. However, in cases of oxygen limitation, additional nitrogenous gases such as nitric oxide (NO) and nitrous oxide (NO 2 ) are produced [6,9,10]. In soil management, this negatively affects the efficiency of fertilizer, leading to nitrogen loss for the crops, an increased release of greenhouse gases from the soil, and eutrophication of water bodies downstream [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations